ANALISIS KESULITAN PADA MATERI OPERASI HITUNG BILANGAN PECAHAN KELAS IV SEKOLAH DASAR - Fitri Anisa Lubis; Rohana Yolanda; Anita Meilina Purba; Imelda Indah Sinaga; Andreas Agita Ginting (LPPM Institut Ahmad Dahlan Probolinggo, 2026)
This study aims to analyze the difficulties in learning fraction arithmetic operations among fourth-grade elementary school students. The subjects of this study were three representative students from Grade IV at SD Negeri 060858, Medan Tembung District. The results showed that the overall level of students’ learning difficulties reached 85%, both in understanding the material concepts and in carrying out the operational procedures. The factors contributing to these difficulties include internal and external factors. It is expected that teachers, in teaching fraction arithmetic operations, place greater emphasis on students’ mastery of concepts, principles, and operations. Thus, learning difficulties in fraction arithmetic can be minimized.